A convenient transesterification method for synthesis of AT2 receptor ligands with improved stability in human liver microsomes. Issue 3 (1st February 2018) - Wannberg, Johan; Isaksson, Rebecka; Bremberg, Ulf; Backlund, Maria; Sävmarker, Jonas; Hallberg, Mathias; Larhed, Mats
Graphical abstract: Highlights: Potent AT2 R ligands were synthesized by a fast transesterification reaction. AT2 R ligands equipotent toC38 with improved metabolic stability were identified. The new compounds retained high AT2 R/AT1 R selectivity. New compounds may be used as tools in rodent models of neuropathic pain. Abstract: A series of AT2 R ligands have been synthesized applying a quick, simple, and safe transesterification-type reaction whereby the sulfonyl carbamate alkyl tail of the selective AT2 R antagonist C38 was varied. Furthermore, a limited number of compounds where acyl sulfonamides and sulfonyl ureas served as carboxylic acid bioisosteres were synthesized and evaluated. By reducing the size of the alkyl chain of the sulfonyl carbamates, ligands7a and7b were identified with significantly improved in vitro metabolic stability in both human and mouse liver microsomes as compared to C38 while retaining the AT2 R binding affinity and AT2 R/AT1 R selectivity. Eight of the compounds synthesized exhibit an improved stability in human microsomes as compared to C38.